Selenium biofortification improves nutraceutical quality and antioxidant capacity of lettuce (Lactuca sativa L.) - Buendía-García, Alain; Lozano-Cavazos, Carlos Javier; Rodríguez-Ortiz , Juan Carlos; Carballo-Méndez, Fernando de Jesús; Moreno-Reséndez, Alejandro; Sariñana-Navarrete, María de los Ángeles; Preciado-Rangel, Pablo (Ecosistemas y Recursos Agropecuarios, 2021)
Selenium (Se) is an essential micronutrient for humans and its deficiency affects 15% of the world’s population. Agronomic biofortification improves the biosynthesis of bioactive compounds and promotes their bioaccumulation. In the present work, the effect of foliar application of Se on yield, biosynthesis of bioactive compounds and accumulation in lettuce (Lactuca sativa L.) cv “Parris Island cos”. was evaluated. Five treatments were used: 0, 10, 20, 40 and 60 μ M L-1. Biofortification with the biosynthesis of phytochemical compounds and their concentration in lettuce leaves was positively modified, without affecting the yield. Se foliar spraying is an alternative to increase the biosynthesis of phytochemical compounds and increase the concentration of this element in lettuce with the possibility of improving public health with its consumption.